The Winged Bull in the Assyrian Civilization- A Semiotic Perspective - عباس, حيدر فاضل (ALBAHITH ALALAMI, 2016)
Every cultural achievement is a creative text, and every text is a group of signs. The Winged Bull sculpture is a sort of text that is not confined to some signs; indeed, its cultural signs go far beyond as they are open-ended, everlasting and it lends itself to various horizons of interpretation. The recipient has to combine the signs of this sculpture, which belong to different patterns, in the pursuit for perfection so that he can decode its media message. I have tackled this sculpture by adopting a semiotic approach. The semiotic approach is a modern critical approach which is as wide as culture and as rich as knowledge. It has been linked to modernism, which in turn has been linked to modern critical approaches, because it can generate new cognitive frameworks instead of the continuous production of knowledge alongside stereotyped patterns which exhausted their interpretive ability. With this new and original cognitive momentum generated by these approaches, man’s view of literature, culture, things and the environment around him changed, and man can no longer view them in the same old-fashioned way, because his view of the world has changed.